CLASSROOM MANAGEMENT STRATEGIES AND CHALLENGES IN EFL SPEAKING CLASS - Rokhaniyah, Hesti; Ardiyanti, Dwi; Susilowati, Ida; Virgiyanti, Diska Fatima; Nuraini, Eka Indah (University of Kuningan, 2024)
Classroom management involves all endeavors aimed at establishing an efficient and pleasant teaching and learning environment that can inspire learners to learn effectively based on their abilities. It encompasses a range of intentional activities conducted by lecturers with the goal of establishing and sustaining optimal conditions for the teaching and learning process. This research investigates practical management strategies for English as a Foreign Language (EFL) speaking class. Semi-structured interviews and active classroom observation were employed to collect the data. Three EFL lecturers from the English Department of Universitas Darussalam Gontor who provided English speaking classes participated in this study. The objective was to look into the lecturers' viewpoints and management of speaking classes and to examine the strategies they employed and the challenges they experienced. The findings show that the lecturers had implemented a variety of strategies, including setting discipline, physical environment, encouraging more usage of English, offering engaging topics, speaking correction techniques, and building excitement for content. The results also revealed that the lecturers encountered difficulties to manage their teaching. Challenges such as improper pronunciation, learners' low self-esteem, and shortage of lexical resources were among the lecturers’ obstacles.